Elemental and spectroscopic characterization of plasters from Fatih Mosque-Istanbul (Turkey) by combined micro-Raman, FTIR and EDXRF techniques - Güleç, Ahmet; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2015)
The characterization of the plasters and coloring agents of the wall paintings of Fatih Mosque have been performed using combined micro-Raman, FTIR and EDXRF techniques. The investigations show that the plaster used on the walls has mixed gypsum lime binders. Cinnabar {HgS}, lead red {Pb3O4} and hematite {alpha-Fe2O3} were identified in the red surfaces. Blue color is attributed to ultramarine blue {Na8-10Al6Si6O24S2-4}. Green color is assigned to mixtures of green earth, copper phthalocyanine {Cu(C32Cl16N8)} and brochantite {CuSO4 center dot 3Cu(OH)(2)}. Strontium yellow {SrCrO4} and zinc white {ZnO} were also used to ensure the color tone. The results provide a basis for future restoration of wall paints. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: EDXRF; Fatih Mosque; FTIR; Micro-Raman; Plasters; Wall paints; Reflection Ftir; Pigments; Paintings; Minerals; Mortars; Spectra